Modern methods of monitoring and assessing the current status of athletes-combatants in real time - Puhach, Yaroslavna; Druz, Valeriy; Yefremenko, Andriy; Revenko, Valeriy; Galashko, Mykola; Shutieiev Vjаcheslav; Nizhevskaya, Tetyana; Miroshnichenko, Valery (Slobozhanskyi Herald of Science and Sport, 2019)
Purpose: to establish the most effective methods of monitoring and evaluating the current status of athletes, and on the basis of this, develop methods for remote monitoring of the current state of martial arts in the process of conducting a duel. Materials & Methods: videotapes of competitive fights of athletes participating in Ukrainian championships, world championships, and Olympic Games were used in the research. The methods used are: «high-speed video filming» a biomechanical analysis of the kinematic displacements of the total center of mass of an athlete and individual bio-kinematic parts of the body, followed by the determination of the dynamic efforts that ensure their movement, as well as the statistical stress that determines the availability of these efforts. Results & Conclusions: the use of modern technical video recording tools and computer equipment with appropriate programs for processing video sequences of performed movements and on the basis of established regularities of the flow of biodynamic efforts of competitive movements of martial sportsmen opens up broad possibilities for developing methods for remote contactless monitoring of the current status of athletes.